PENGARUH PENGGUNAAN INSTAGRAM TERHADAP PARTISIPASI POLITIK PEMILIH PEMULA PEMILIHAN UMUM PRESIDEN RI 2019 - Anggraini, Devianti; Ariesta, Aang Wahyu; Wuryanta, A.G. Eka Wenats (Interaksi: Jurnal Ilmu Komunikasi, 2022)
This research aims to show of how many impact, instagram as a sosial media, effected the newly voters at 2019 Indonesian presidential election. The research method is explanation quantitative through survey on spreading questionaire to respondents. The population of that respondents are 150 Paramadina students of 2015 and 2016 Communication Majors. On this research, there are strong relations between frequencies-agresive behaviour on scale 0.717. Moderate relations between duration-agressive behavior on scale 0.573, and strong relations between intensityagressive behaviour (0.729). Relations between utilization of instagram as a variable dimension and new voters were very strong, with 0.802 scale. By those calculation above, we could draw a conclusion that the correlation on utilization of instagram and the participation of new voters have the coefficient correlations (r) = 0.802 (very strong), then we get R² contribution from regretions= 64.4%. It means that the utilizations of instagram as a media, contribute as much as 64.4% on new voters political participations for Paramadina students of 2015 and 2016 Communication Majors.